Distribution of Isomorphous Salts between Aqueous and Solid Phases in Ternary Systems: Zinc-Ammonium Sulphate-Magnesium Ammonium Sulphate-H2O systems - Madhurambal, G.; Hariharan, S.; Ramasamy, P. (Asian Journal of Chemistry, 2010)
Abu Elamayem Equation, the advanced equation of Domer Hoskins and Kholpin's equations relate the distribution of ismorphous salts between solid and aqueous phases during non-equilibrium crystallization. The distribution of isomorphous salts zinc ammonium sulphate and magnesium ammonium sulphate between aqueous and solid phases in the ternary system has been studied at different concentrations of less soluble salt in the ternary systems. Experimental results have been explained by a proper choice of values of the parameters in Abu Elemeyam's equation. These parameters characterize a given system over a wide range of concentration and by the use of the parameters, the amount of less soluble salt crystallizing out of the ternary systems can be predicted.